Diversity of Nigrospora (Xylariales, Apiosporaceae) Species Identified in Korean Macroalgae Including Five Unrecorded Species - Wonjun Lee; Dong-Geon Kim; Rekhani H. Perera; Ji Seon Kim; Yoonhee Cho; Jun Won Lee; Chang Wan Seo; Young Woon Lim (Mycobiology, 2023)
Nigrospora (Xylariales, Apiosporaceae) consists of species of terrestrial plant endophytes and pathogens. Nigrospora has also been reported in marine environments such as mangroves, sea fans, and macroalgae. However, limited research has been conducted on Nigrospora associated with macroalgae. Here, we isolated Nigrospora species from three types of algae (brown, green, and red algae) from Korean islands (Chuja, Jeju, and Ulleung) based on phylogenetic analyses of multigenetic markers: the internal transcribed spacers (ITS), beta-tubulin (BenA), and translation elongation factor 1 (TEF1-α). A total of 17 Nigrospora strains were isolated from macroalgae and identified as nine distinct species. The majority of Nigrospora species (seven) were found on brown algae, followed by red algae (three), and then green algae (two). To our understanding, this study represents the first account of N. cooperae, N. covidalis, N. guilinensis, N. lacticolonia, N. osmanthi, N. pyriformis, and N. rubi occurring in marine environments. Additionally, this study provides the first report of the occurrence of N. cooperae, N. covidalis, N. guilinensis, N. lacticolonia, and N. osmanthi in South Korea. This study will provide valuable insights for future research exploring the functions of fungi in macroalgal communities.